2021
DOI: 10.1371/journal.pone.0248364
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and phenotypic characterization of Fusarium oxysporum f. sp. niveum isolates from Florida-grown watermelon

Abstract: Fusarium wilt of watermelon (Citrullus lanatus) caused by Fusarium oxysporum f. sp. niveum (Fon), has become an increasing concern of farmers in the southeastern USA, especially in Florida. Management of this disease, most often through the use of resistant cultivars and crop rotation, requires an accurate understanding of an area’s pathogen population structure and phenotypic characteristics. This study improved the understanding of the state’s pathogen population by completing multilocus sequence analysis (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This was in conformity with Bashir et al 12 who worked on the effect of sodium carbonate and sodium chloride for the control of black rot disease of Mangifera indica caused by Aspergillus niger, much resistance was also observed by the pathogen even though conidia germination is hindered. Fulton, et al 13 also worked on the fungi diseases of watermelon and found Alternaria leaf blight (Alternaria cucumerina), Anthracnose (Colletotrichum orbiculare), Cercospora leafspot (Cercospora citrullina), downy mildew (Pseudoperonospora cubensis), Fusarium wilt (Fusarium oxysporum), Gummy stem blight (Didymella bryoniae) and powdery mildew (Podosphaera xanthii) affecting the growth of watermelon. He also opined that disease severity is high in areas where there is frequent rainfall and temperatures are high, a characteristic nature of Anyigba where this research was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…This was in conformity with Bashir et al 12 who worked on the effect of sodium carbonate and sodium chloride for the control of black rot disease of Mangifera indica caused by Aspergillus niger, much resistance was also observed by the pathogen even though conidia germination is hindered. Fulton, et al 13 also worked on the fungi diseases of watermelon and found Alternaria leaf blight (Alternaria cucumerina), Anthracnose (Colletotrichum orbiculare), Cercospora leafspot (Cercospora citrullina), downy mildew (Pseudoperonospora cubensis), Fusarium wilt (Fusarium oxysporum), Gummy stem blight (Didymella bryoniae) and powdery mildew (Podosphaera xanthii) affecting the growth of watermelon. He also opined that disease severity is high in areas where there is frequent rainfall and temperatures are high, a characteristic nature of Anyigba where this research was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…While DNA extraction and PCR assays require specialized tools, they have become more routine for diagnosis in plant pathology and more widely distributed [39][40][41]. In comparison, the bioassay requires more resources and time to grow multiple different crop hosts before completing the diagnosis (Tables 2 and 3) [23,24,42]. Even then, nonpathogenic strains may not be isolated.…”
Section: Evaluation Of Diagnostic Methodsmentioning
confidence: 99%
“…2021, 22, x FOR PEER REVIEW 4 of 15 aggressiveness than race 1 isolates. This has been argued due to multiple isolates of the same race being tested and showing variation within their aggressiveness [23,24]. Fon is found in most, if not all, watermelon growing regions in the world [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, TEF-1α, β-tubulin and histone 3 regions have been explored by Webb et al [ 48 ] and Taha et al [ 49 ] for dissecting the genetic variability among F. oxysporum isolates. Recently, Fulton et al [ 50 ] employed two different housekeeping genes (BT and TEF) for analyzing the phylogenetic kinship of F. oxysporum f. sp. niveum isolates from the major watermelon-producing regions in north, central, and south Florida.…”
Section: Introductionmentioning
confidence: 99%